Study of Bc+→J/ψDs+ $$ {\mathrm{B}}_{\mathrm{c}}^{+}\to \mathrm{J}/\psi {\mathrm{D}}_{\mathrm{s}}^{+} $$ and Bc+→J/ψDs∗+ $$ {\mathrm{B}}_{\mathrm{c}}^{+}\to \mathrm{J}/\psi {\mathrm{D}}_{\mathrm{s}}^{\ast +} $$ decays in pp collisions at s $$ \sqrt{\mathrm{s}} $$ = 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2022)
Keywords : B Physics, Hadron-Hadron Scattering.; Springer Open.